Novel IFNγ homologue identified in Nile tilapia (Oreochromis niloticus) links with immune response in gills under different stimuli. Issue 71 (December 2017) - Velázquez, Janet; Acosta, Jannel; Herrera, Naylin; Morales, Antonio; González, Osmany; Herrera, Fidel; Estrada, Mario Pablo; Carpio, Yamila
Abstract: Interferon gamma (IFN-γ) has important roles in both innate and adaptive immune responses. This cytokine plays a very important role in defining Th1 immune response in all vertebrates. In the present study, we identified and isolated for the first time the gene coding for Nile tilapia ( Oreochromis niloticus ) IFNγ from spleen lymphocytes. The isolated tilapia IFNγ has between 24 and 62% of amino acid identity as compared to reported sequences for other teleost fishes. It has close phylogenetic relationships with IFNγ molecules belonging to the group of Perciforms and presents the typical structural characteristics of gamma interferon molecules. The tissue expression analysis showed that IFNγ is expressed constitutively in head kidney, skin, intestine, muscle and brain. Its expression was not detected in gills by conventional RT-PCR. However, under conditions of stimulation with Poly I:C and LPS, IFNγ expression was up-regulated in gills after 24 h post-stimulation. IFNγ expression was also induced in gills 24 h after Edwardsiella tarda infection suggesting its important role in immunity against intracellular bacteria. The recombinant protein produced in Escherichia coli induced Mx gene transcription in head kidney primary culture cells. These results are the first steps to characterize the role of tilapia IFNγ in the defense against pathogens in tilapia. Furthermore, the isolation of this molecule provides a new tool to characterize the cellular immune response to various stimuli in this organism. Highlights: A novel Nile tilapia IFNγ was cloned from spleen lymphocytes stimulated with LPS. The isolated cDNA sequence has the typical features of IFNγ. IFNγ expression was induced in gills 24 h after stimulation with poly I:C and LPS. E. tarda infection induces IFN expression levels in gills 24 h after infection. Recombinant IFNγ activates Mx gene transcription in head kidney primary culture cells.